Potential for ultrafast dynamic chemical imaging with few-cycle infrared lasers - Morishita, Toru; Le, Anh-Thu; Chen, Zhangjin; Lin, C. D. (My University, 2008)
We studied the photoelectron spectra generated by an intense few-cycle infrared laser pulse. By focusing on the angular distributions of the back rescattered high energy photoelectrons, we show that accurate differential elastic scattering cross-sections of the target ion by free electrons can be extracted. Since the incident direction and the energy of the free electrons can be easily changed by manipulating the laser's polarization, intensity and wavelength, these extracted elastic scattering cross-sections, in combination with more advanced inversion algorithms, may be used to reconstruct the effective single-scattering potential of the molecule, thus opening up the possibility of using few-cycle infrared lasers as powerful table-top tools for imaging chemical and biological transformations, with the desired unprecedented temporal and spatial resolutions.